Company analysis "hot burger" / Mohammad Rafiqi Saad, Mohamad Haizal Abdul Ghaffar Cheong and Muhammad Shakil Mohamad - Saad, Mohammad Rafiqi; Abdul Ghaffar Cheong, Mohamad Haizal; Mohamad, Muhammad Shakil (2017)
For this case study which about how this company sell their product and how they as local brand product use marketing, operational strategy and also target market to gain their profit. From this company, we can see how their operate their company to maintained their regular customer by providing services and good product to the consumer or customer. Besides that, from this case study too we also can see how this kind of business growth and able to identify their quality. Not only that, we also can provides some alternatives, recommendations and improvement that this company can do to achieve a good company. Last but not least, from this report we can learn regarding what we can do or don't when we as student before want to establish company and growth more consistently and gain more profit with lower cost of marketing, production, and raw materials.